Leisure Sedentary Behavior and Risk of Lung Cancer: A Two-Sample Mendelian Randomization Study and Mediation Analysis - Gao, Yan; Mi, Jiarui; Liu, Zhengye; Song, Qibin (Frontiers in Genetics, 2021)
Leisure sedentary behavior, especially television watching, has been previously reported as associated with the risk of lung cancer in observational studies. This study aims to evaluate the causal association with two-sample Mendelian randomization (MR) analysis. Single nucleotide polymorphisms associated with leisure television watching, computer use, and driving were extracted from genome-wide association studies. Summary-level results of lung cancer overall and histological types were obtained from International Lung Cancer Consortium (ILCCO). In univariable MR using inverse-variance-weighted method, we observed causal effects of television watching on lung cancer (OR, 1.89, 95% confidence interval [CI], 1.41, 2.54; p=2.33×10–5)), and squamous cell lung cancer (OR, 2.37, 95% CI, 1.58, 3.55; p=3.02×10–5), but not on lung adenocarcinoma (OR, 1.40, 95% CI, 0.94, 2.09; p=0.100). No causal effects of computer use and driving on lung cancer were observed. Television watching significantly increased the exposure to several common risk factors of lung cancer. The associations of television watching with lung cancer and squamous cell lung cancer were compromised after adjusting for smoking quantity with multivariable MR. Our mediation analyses estimated indirect effects of television watching on lung cancer (beta, 0.31, 95% CI, 0.13, 0.52; p= 6.64×10–4) and squamous cell lung cancer (beta, 0.33, 95% CI, 0.14, 0.53, p= 4.76×10–4) mediated by smoking quantity. Our findings indicate that television watching is positively correlated with the risk of lung cancer, potentially mediated through affecting smoking quantity.